Impact of conflicting information on the use of antirheumatic drugs in pregnancy and breastfeeding: perspectives of healthcare providers from the global PRAISE survey - Karen Schreiber; Christine Graversgaard; Ioannis Parodis; Nancy Agmon-Levin; Silvia Aguilera; Aleksandra Antovic; George K. Bertsias; Ilaria Bini; Anca Bobirca; Susana Capela; Ricard Cervera; Nathalie Costedoat-Chalumeau; et al. (Therapeutic Advances in Musculoskeletal Disease)
Background: Treating rheumatic musculoskeletal diseases (RMDs) during pregnancy and breastfeeding presents significant complexities, mainly due to inconsistencies between the clinical guidance documents and the reference safety information, including the summary of product characteristics (SmPC) and the patient information leaflets (PIL). Objectives: To assess healthcare professionals’ (HCPs) prescribing behaviors, comfort levels, and challenges when advising patients, focusing on discrepancies between clinical guidance documents and SmPC/PIL. Design: Online survey entitled PRAISE (Perception of healthcare providers Regarding Antirheumatics in pregnancy and breastfeeding: advice, Information and patient perSpEctives) and disseminated through HCPs groups and social media. Methods: A cross-sectional survey was conducted among 414 HCPs globally. Respondents were divided into prescribers ( n  = 336) and non-prescribers ( n  = 78) based on their self-reported role in prescribing antirheumatic medications to pregnant or breastfeeding patients with RMDs. The survey covered demographics, clinical experience, confidence in prescribing, use of clinical guidelines, and experiences managing conflicting information between guidelines and SmPC/PIL. Results: Prescribers were more likely than non-prescribers to feel comfortable discussing medication safety during pregnancy. Most prescribers found clinical guidance documents useful, with 48% rating them as “very useful” and 38% as “extremely useful.” In case of conflicting information between clinical guidance documents and SmPC/PIL, 58% of HCPs reported that it caused confusion and tension in patient–doctor relationships, and almost 20% of them are “likely” or “very likely” to discontinue ongoing treatment. Clear communication and shared decision-making were the most common strategies used to address patient concerns. Conclusion: HCPs often face significant challenges when advising patients with RMDs on the use of medications during pregnancy and breastfeeding. Conflicting information between clinical guidance documents and SmPC/PIL can disrupt patient–doctor relationship and lead to treatment discontinuation, with potential consequences on maternal disease control. Improved alignment between clinical guidance documents and the SmPC/PIL could enhance patient care and prevent confusion among HCPs and patients.